2010
DOI: 10.4103/0971-5851.73603
|View full text |Cite
|
Sign up to set email alerts
|

Primary plasma cell leukemia with light chain secretion and multiple chromosomal abnormalities: How successfully treated? - A case report with review of literature

Abstract: Primary plasma cell leukemia is a rare form of plasma cell dyscrasia. We present a case which had leukocytosis with numerous circulating plasma cells in the peripheral blood. Flow cytometry revealed an unusual CD117 expression. Free light chain analysis in the serum showed a markedly elevated level of free lambda light chains. Radiography did not reveal any lytic lesions. Fluorescent in-situ hybridization analysis revealed deletion of 13q14.3 and t(4;14)/t(11;14), while the cytogenetic analysis was normal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Recent attempts at genetic and molecular profiling of PCL have shown cytogenetic abnormalities in over 70% of PCL patients [10]. Hypodiploidy and complex karyotypes with multiple numerical and structural abnormalities involving chromosome 1, 13 and 14 are reported in a significant number of PCL cases [4,5,11] including report from India of multiple cytogenetic abnormality in a case of pPCL [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts at genetic and molecular profiling of PCL have shown cytogenetic abnormalities in over 70% of PCL patients [10]. Hypodiploidy and complex karyotypes with multiple numerical and structural abnormalities involving chromosome 1, 13 and 14 are reported in a significant number of PCL cases [4,5,11] including report from India of multiple cytogenetic abnormality in a case of pPCL [12].…”
Section: Discussionmentioning
confidence: 99%
“…In pPCL, the efficacy of combinations of novel agents, such as lenalidomide, bortezomib, and dexamethasone (RVD), 84 bortezomib, thalidomide, and dexamethasone (VTD), 61,64,71 or melphalan, prednisone, bortezomib, and thalidomide (VMPT), 71 appears very promising. Studies describing these regimens invoke only a small numbers of patients but are based on the biologic and clinical features seen.…”
Section: Combinations Of Novel Agentsmentioning
confidence: 99%
“…In fact, bortezomib, lenalidomide and dexamethasone combination therapy (VRD regimen) is highly effective in the treatment of newly diagnosed myeloma (14). There have been only two case reports of PCL patients treated with VRD therapy (15,16) (Table). One case was primary PCL and two cases were secondary PCL.…”
Section: Discussionmentioning
confidence: 99%
“…One case was primary PCL and two cases were secondary PCL. Goyal et al reported the first primary PCL patient who obtained a complete remission after receiving combination chemotherapy with bortezomib, lenalidomide and dexamethasone (15). However, the details of the treatment regimen and the patient's clinical course were not described.…”
Section: Discussionmentioning
confidence: 99%